Catalytic pyrolysis and non-catalytic pyrolysis of sugarcane bagasse: Product yield and bio-oil characterization - Jamilatun Siti; Nurmustaqimah (BIO Web of Conferences)
Utilizing pyrolysis to convert biomass, biomass is an exceptionally promising and environmentally sustainable alternative source of renewable energy. This study investigates the impact of catalysts, specifically activated charcoal and Ni metal-based catalysts, on the pyrolysis outcomes of bagasse at a temperature of 500ºC. The pyrolysis process was conducted with different catalyst weights, namely 2.5 grams and 5 grams, as well as without any catalyst. The quantification of pyrolysis products, such as bio-oil, tar, charcoal, and gas, was conducted by the utilization of a fixed bed reactor. The findings indicate that the utilization of a catalyst has an impact on the pyrolysis yield, albeit resulting in a lower bio-oil yield. The pyrolysis yield was influenced by variations in catalyst weight, with certain instances demonstrating increased bio-oil yields while using a lower catalyst weight. The analysis of the components of bio-oil revealed notable differences depending on the catalyst employed, indicating the possibility of adjusting the features of bio-oil. This study's findings have significant ramifications for applications in the chemical and food industries.